Prediction of vaginal delivery with transperineal ultrasound in women induced with dinoprostone beyond 40 weeks of gestation - Çelik, Hale Göksever; Çelik, Engin; Yıldırım, Gökhan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Digital cervical evaluation has been used to determine the likelihood of vaginal delivery which is considered by many women to be non-tolerable. Recently, transperineal ultrasound allowing direct visualization of the fetal skull has been using for the prediction of labor route. Authors aimed to study whether measurements on transperineal ultrasound are predictive for vaginal delivery in pregnant women induced with dinoprostone at 40.0-42.0 gestational weeks. Methods: A total of 55 pregnant women at 40.0-42.0 gestational weeks were enrolled in this prospective observational study. All participated women were examined before the induction with dinoprostone to measure the head-perineum distance (HPD), the head-pubis distance and the angle of progression of fetal head (AOP). Results: The greater AOP, the shorter HPD and the head-pubis distance were associated with vaginal delivery in the nulliparous women. The HPD and the head-pubis distance were shorter, whereas the AOP was greater in the multiparous women giving birth by vaginal route. Conclusions: Transperineal ultrasound can be applied at the beginning of labor to predict whether vaginal delivery will occur or not. As shown in our study, the pregnant women with shorter HPD and wider AOP might have a high possibility to achieve vaginal delivery.